Lung Transplant for Chronic Obstructive Pulmonary Disease - Swartz, Kyle; Mansour, Ali; Alsunaid, Sammar (Seminars in Respiratory and Critical Care Medicine, 2024)
Chronic obstructive pulmonary disease (COPD) carries a high burden of morbidity and mortality to patient and a high cost to health care systems. Lung transplantation is a last resort available for end-stage COPD patients interested in pursuing it and meeting the strict transplant requirements. It requires commitment from patients and their loved ones to support them through this tough process. This review will cover history of transplant, indications, candidate selection, evaluation testing, transplant listing, type of transplant (single versus bilateral), posttransplant complications, immunosuppression, and rejection. It is tailored to the COPD patient when applicable; however, many aspects of lung transplantation are shared amongst all lung diseases eligible for transplant.
Keywords: lung transplant; chronic obstructive pulmonary disease (COPD); immunosuppression